1989
DOI: 10.1002/anr.1780320207
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy in women with systemic sclerosis

Abstract: We assessed fetal morbidity and mortality in women with systemic sclerosis (SSc). Women with a history of SSc and a concomitant pregnancy completed a detailed questionnaire about the pregnancy. These 48 subjects were age‐matched and race‐matched to 2 other groups of women (a rheumatoid arthritis group and a control group from the same neighborhood), all of whom had been pregnant at least once. There were no differences in the frequencies of miscarriage or perinatal death in the SSc group compared with the 2 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
49
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 123 publications
(49 citation statements)
references
References 14 publications
0
49
0
Order By: Relevance
“…It is likely for this reason that women with SSc in past decades had been strongly advised against pregnancy and often counseled to terminate pregnancies that have occurred [12]. More recently, a series of retrospective and prospective studies have provided more detailed analysis of pregnancy outcomes and have demonstrated that, for most women with SSc, pregnancy outcomes are reasonably good [1318]. Reported rates of early pregnancy loss of 14% ‒ 15% [13, 14] are somewhat increased from the estimated 10% in the general population.…”
Section: Maternal and Fetal Outcomes Of The Ssc Pregnancymentioning
confidence: 99%
See 2 more Smart Citations
“…It is likely for this reason that women with SSc in past decades had been strongly advised against pregnancy and often counseled to terminate pregnancies that have occurred [12]. More recently, a series of retrospective and prospective studies have provided more detailed analysis of pregnancy outcomes and have demonstrated that, for most women with SSc, pregnancy outcomes are reasonably good [1318]. Reported rates of early pregnancy loss of 14% ‒ 15% [13, 14] are somewhat increased from the estimated 10% in the general population.…”
Section: Maternal and Fetal Outcomes Of The Ssc Pregnancymentioning
confidence: 99%
“…More recently, a series of retrospective and prospective studies have provided more detailed analysis of pregnancy outcomes and have demonstrated that, for most women with SSc, pregnancy outcomes are reasonably good [1318]. Reported rates of early pregnancy loss of 14% ‒ 15% [13, 14] are somewhat increased from the estimated 10% in the general population. Late pregnancy losses were few, and generally occurred in women with severe diffuse SSc [14, 16].…”
Section: Maternal and Fetal Outcomes Of The Ssc Pregnancymentioning
confidence: 99%
See 1 more Smart Citation
“…SSc occurs in women of childbearing age approximately five times more frequently than in men 2. Pregnancy outcome studies showed an increased incidence of perinatal loss as well as an increased risk of preterm births and growth retardation in maternal scleroderma 2 3 4 5.…”
mentioning
confidence: 99%
“…SSc occurs in women of childbearing age approximately five times more frequently than in men 2. Pregnancy outcome studies showed an increased incidence of perinatal loss as well as an increased risk of preterm births and growth retardation in maternal scleroderma 2 3 4 5. Detailed studies of placental findings in SSc are limited, and few pathological descriptions showed decidual vasculopathy, placental mesenchymal villous dysplasia, infarcts and reduction of uteroplacental perfusion 5 6 7.…”
mentioning
confidence: 99%